Perubahan Tenaga Pendidik dan Dampaknya Terhadap Budaya Sekolah Serta Kinerja Pembelajaran (Studi Kasus di SMPIT Al Ichwan Cikarang Utara, Kabupaten Bekasi) - Kristina Damayanti; Maman Suryaman (CV. Rayyan Dwi Bharata, 2026)
Changes in teaching staff are an inherent part of the dynamics of educational organizations and may affect the stability of school culture and the quality of learning. This study aims to analyze the impact of changes in teaching staff on school culture and learning performance from the perspective of the school as a learning organization. This research employed a qualitative approach with a case study design conducted at SMPIT Al Ichwan, North Cikarang, Bekasi Regency, involving 21 teachers, 175 students, and 3 supporting staff. The findings reveal that changes in teaching staff, particularly due to the transfer of senior teachers, lead to shifts in school culture, decreased student discipline, and weakened learning systems. These findings are supported by quantitative data showing a teacher absenteeism rate of 23%, student tardiness at 38%, and unimplemented learning schedules at 31%. From the perspective of a learning organization, the school has not been able to optimally implement the five core disciplines. This study concludes that structural changes without strengthening leadership and organizational culture may lead to dysfunction in the educational system.